Scientific rationale for a higher dose of nusinersen. Issue 6 (13th May 2022) - Finkel, Richard S.; Ryan, Monique M.; Pascual Pascual, Samuel Ignacio; Day, John W.; Mercuri, Eugenio; De Vivo, Darryl C.; Foster, Richard; Montes, Jacqueline; Gurgel‐Giannetti, Juliana; MacCannell, Drew; Berger, Zdenek
Abstract: Objective: The long‐term favorable safety profile of nusinersen provides an opportunity to consider a higher dose. We report on the relationships between nusinersen cerebrospinal fluid (CSF) exposure, biomarker levels, and clinical efficacy. Methods: The analyses used data from the CS3A and ENDEAR studies of nusinersen in participants with infantile‐onset spinal muscular atrophy (SMA). Steady‐state CSF trough ( C trough ) levels, plasma phosphorylated neurofilament heavy chain (pNF‐H) levels, body weight, and Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) scores were selected as parameters of interest. A validated population pharmacokinetic (PK) model was applied to predict the nusinersen CSF C trough . PK/pharmacodynamic (PK/PD) models used nusinersen CSF C trough measurements, which were time‐matched with CHOP INTEND scores. Results: Higher nusinersen CSF exposure was associated with a greater decrease in pNF‐H levels and greater efficacy, as measured by change in the CHOP INTEND score from baseline. These findings indicate a dose–response relationship between CSF nusinersen levels and treatment response. The higher dose is predicted to lead to approximately a 2.4‐fold increase in nusinersen CSF levels with fewer loading doses. PK/PD modeling indicates that a higher concentration of nusinersen may predict an additional 5‐point increase in CHOP INTEND score beyond that observed with 12 mg. Interpretation: Our data indicate that a higher dose of nusinersen may lead to additional clinically meaningful improvement in efficacy when compared with the currently approved 12‐mg dose. The efficacy, safety, and PK of a higher nusinersen dose are currently under investigation in the ongoing phase 2/3 DEVOTE study (NCT04089566).